110k views
1 vote
Solve by factoring
y {}^(2) - 4y - 12 = 0

Solve by factoringy {}^(2) - 4y - 12 = 0-example-1
User Vafylec
by
5.3k points

1 Answer

1 vote

\begin{gathered} \text{ To solve }y^2-4y-12=0\text{ by factorization method} \\ \end{gathered}
\begin{gathered} y^2-4y-12=0\text{ } \\ =y^2-6y+2y-12=0 \\ =y(y-6)+2(y-6)=0 \\ (y-6)\text{ is a common factor} \\ =(y-6)(y+2)=0 \\ y-6=0\text{ and y+2=0} \\ y=6\text{ and y=-2} \end{gathered}

The answer is y = 6 and y= -2

User Darian Miller
by
5.0k points